A high-adhesion and high-permeability ceramic ink and its preparation and application method
By using high adhesion and high permeability ceramic ink during the inkjet printing process of ceramic tile, pre-spraying needle-shaped nano calcium carbonate and nickel stearate, the problem of glaze ink separation is solved, uniform coloring and high adhesion of the surface of the ceramic tile is achieved, and the quality of the ceramic tile is improved.
Patent Information
- Application Number
- CN202411407465.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-10-10
AI Technical Summary
During the inkjet printing process of ceramic tile, oil solvent-based ink can easily lead to separation of glaze ink, resulting in uneven color on the surface of the ceramic tile and uneven glaze surface, affecting the quality of the ceramic tile.
A high-adhesion and high-permeability ceramic ink is used to improve the permeability and adhesion of the ink by pre-spraying components such as needle-shaped nano calcium carbonate and nickel stearate to avoid separation of glaze ink.
It achieves uniform coloring and high adhesion on the surface of the tiles, avoids glaze and ink separation, and significantly improves the beauty and quality of the tiles.
Smart Images

Figure BDA0005077053140000021 
Figure BDA0005077053140000061 
Figure BDA0005077053140000062
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ceramic ink, and in particular to a high-adhesion and high-permeability ceramic ink and a preparation and application method thereof. Background Art
[0002] The structure of ceramic tiles usually includes a brick layer, a makeup layer, an inkjet printing layer, and a glaze layer, which are connected in sequence to form the whole of the ceramic tile. However, in the production process of ceramic tiles, especially in the application of inkjet printing technology, there are some technical difficulties that directly affect the appearance and quality of ceramic tiles. At present, many manufacturers use oil-solvent inks for inkjet printing, but in actual use, the problem of glaze-ink separation is often encountered during glazing. This phenomenon causes uneven color and uneven glaze on the surface of the ceramic tile, which seriously affects the quality of the finished ceramic tile.
[0003] The occurrence of glaze-ink separation is closely related to the composition of the ink and the production process of the tile. The main components of oil-solvent ink are solvents and pigments, among which the role of the solvent is to help the pigment to be evenly distributed and dry quickly during the printing process. However, this type of solvent is usually insoluble in water. When the glaze of the tile contains too much water or the glaze line of the production line is too short, the quick-drying property of the ink becomes a key issue. The so-called quick-drying property of the ink refers to the speed at which the ink penetrates into the glaze after being printed on the surface of the tile. If the ink penetrates into the glaze for too long, it may cause the pattern to bleed, thereby reducing the clarity and resolution of the printed pattern. This bleed phenomenon not only affects the aesthetics of the pattern, but also causes the glaze layer to peel off on the surface of the fully glazed tile, further damaging the overall quality of the tile.
[0004] In actual operation, insufficient glaze line length or excessive glaze moisture will affect the quick drying of oil-solvent ink. Since oil-solvent ink itself is incompatible with the moisture in the glaze, when the glaze has more moisture, it is difficult for the ink to dry quickly and penetrate the glaze, which makes the ink spread on the glaze, causing edge seepage. The edge seepage phenomenon not only makes the printed pattern blurred, but also affects the edge sharpness of the pattern, resulting in reduced resolution. In addition, in the production of fully polished glazed tiles, the presence of the glaze layer makes the glaze-ink separation more obvious, and the glaze layer is prone to fall off after polishing, forming an uneven glaze surface, which further reduces the visual effect and practicality of the tiles. Summary of the invention
[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a high-adhesion and high-permeability ceramic ink and a preparation and application method thereof.
[0006] The above object of the present invention is achieved through the following technical solutions:
[0007] A high-adhesion and high-permeability ceramic ink, comprising a pre-coating material and a coloring material, wherein the pre-coating material is sprayed on the surface of the tile before the coloring material, and the coloring material is sprayed after the pre-coating material is dried;
[0008] Wherein, the coloring material comprises the following components in parts by weight:
[0009]
[0010]
[0011] The pre-coating material comprises the following components in parts by weight:
[0012] 50-100 parts of deionized water;
[0013] Ethanol 50-100 parts;
[0014] 20-35 parts of needle-shaped nano calcium carbonate.
[0015] The above technical solution, through pre-spraying and combined with the application of needle-shaped nano calcium carbonate, presents many advantages when penetrating the makeup soil layer. First, after the nano calcium carbonate penetrates the makeup soil layer, it still maintains a high porosity, thereby ensuring that the overall porosity of the makeup soil layer is not significantly affected. This is crucial because the porosity of the makeup soil layer is directly related to the penetration effect of the colorant. When the makeup soil layer has a suitable porosity, the colorant can penetrate more smoothly and be evenly distributed in the makeup soil layer. This lays a good foundation for the subsequent coloring process, thereby achieving a more uniform and vivid color performance.
[0016] Secondly, the needle-shaped nano calcium carbonate can not only effectively penetrate into the interior of the cosmetic soil layer, but also some of its particles will remain on the surface of the cosmetic soil layer. This phenomenon brings about significant changes in the surface properties. The needle-shaped nano calcium carbonate has a higher specific surface area, which makes the surface of the cosmetic soil layer rougher. This increase in surface roughness is of great help to the adhesion of the colorant. When the colorant is sprayed onto the surface of the treated cosmetic soil layer, the higher specific surface area can provide more attachment points, making the colorant more firmly fixed to the surface. This not only improves the adhesion of the iron red material, but also avoids problems such as blurred patterns caused by sliding or falling off of the iron red material.
[0017] In addition, the unique structure and properties of needle-shaped nano-calcium carbonate also facilitate the penetration of organic solvents. In this technical solution, propylene glycol methyl ether acetate is selected as the organic solvent, combined with hydrogenated castor oil as a dispersant. The permeability of these two ingredients in the cosmetic soil layer directly affects the distribution of the colorant and the final presentation effect. The role of needle-shaped nano-calcium carbonate in the cosmetic soil layer is similar to a "channel" or "guiding layer". It can absorb and guide organic solvents into the cosmetic soil layer faster, thereby accelerating the overall penetration process of the colorant.
[0018] A common challenge is the "edge seepage" phenomenon that may occur during the infiltration process of the colorant. The so-called "edge seepage" refers to the uneven diffusion of the iron red material in the makeup soil layer, which leads to blurred color boundaries and affects the clarity and resolution of the final printed pattern. The use of needle-shaped nano-calcium carbonate as a regulating material can effectively solve this problem. Because the needle-shaped nano-calcium carbonate has a high specific surface area, it can quickly absorb the organic solvent propylene glycol methyl ether acetate in the colorant, so that the solvent is quickly fixed after entering the makeup soil layer, thereby avoiding excessive diffusion of the iron red material. This process ensures the clarity of the color boundary and ultimately presents a high-resolution pattern.
[0019] Furthermore, the pre-coating material also includes 10-20 parts by weight of nickel stearate, 6-10 parts by weight of disodium ethylenediaminetetraacetate and 5-8 parts by weight of keratin hydrolyzate.
[0020] Nickel stearate is a metal salt of stearic acid, containing nickel ions (Ni 2 +). The combination of nickel ions and stearic acid makes its surface adsorption stronger, with the characteristics of metal-carboxylate, and can form a stronger bond with the surface of nano calcium carbonate particles. When nickel stearate is added to the pre-coating material, the nickel ions in the nickel stearate can form a multi-point coordination bond with the surface of nano calcium carbonate, and its carboxyl part can be combined with the -OH group on the surface of calcium carbonate through hydrogen bonding, so that the properties of the surface of calcium carbonate undergo a lasting surface modification. Through this surface modification, nickel stearate forms a strong hydrophobic protective layer on the surface of calcium carbonate particles, significantly reducing the mutual attraction between particles, thereby improving the dispersibility of calcium carbonate.
[0021] This improvement in dispersibility is of great significance in practical applications. Good dispersibility ensures that calcium carbonate particles can be evenly distributed in the pre-coating material, avoiding the rough surface and unevenness formed by particle aggregation. More importantly, the surface of calcium carbonate particles treated with nickel stearate shows higher lipophilicity. This lipophilicity has a direct impact on the subsequent colorant spraying and penetration process.
[0022] In the coloring process, the coloring material usually contains organic solvents and dispersants, such as propylene glycol methyl ether acetate and hydrogenated castor oil. The main function of these organic solvents and dispersants is to promote the uniform penetration of the coloring material in the cosmetic soil layer, so as to achieve the desired coloring effect. However, the pore structure and surface characteristics of the cosmetic soil layer determine the penetration efficiency of the organic solvent and dispersant. If the surface of the calcium carbonate particles is highly hydrophilic, the solvent may be difficult to effectively penetrate due to poor wettability when in contact with it, which will affect the diffusion and distribution of the coloring material in the cosmetic soil layer.
[0023] The introduction of nickel stearate has effectively changed this situation. As nickel stearate covers the surface of calcium carbonate particles, the lipophilicity of calcium carbonate increases, which means that organic solvents and dispersants can penetrate more smoothly when they come into contact with the modified calcium carbonate. This increase in lipophilicity makes it easier for the organic components in the colorant to migrate into the interior of the cosmetic soil layer, thereby ensuring that the colorant can penetrate into the soil layer and be evenly distributed therein, ultimately achieving stable color presentation.
[0024] On the other hand, calcium carbonate modified with nickel stearate not only improves the permeability of the colorant, but also improves the adhesion of the colorant on the surface of the cosmetic soil layer to a certain extent. During the spraying process, the colorant first contacts the surface of the cosmetic soil layer and gradually penetrates. If the surface particles are not lipophilic enough, the colorant may "slip", affecting its uniformity and adhesion. Nickel stearate avoids this problem by changing the physical and chemical properties of the calcium carbonate surface, making it easier to form a good wetting effect with organic solvents.
[0025] Secondly, the added keratin hydrolyzate contains complex amino acids. On the one hand, the complex amino acids have multiple functional groups (such as amino, carboxyl, hydroxyl, etc.), which can form multi-point adsorption with the surface of nano-calcium carbonate, and can effectively control the relative strength of hydrophilicity and lipophilicity on the surface of nano-calcium carbonate, so as to form a stronger interaction with the organic solvent and dispersant in the colorant, so as to make the colorant more permeable. On the other hand, the metal ions of nickel stearate and the complex amino acids will also produce synergistic adsorption on the surface of nano-calcium carbonate, providing a more stable surface.
[0026] Furthermore, the complex amino acids contained in the keratin hydrolyzate can affect the morphology of calcium carbonate crystals, and nickel stearate has the function of stabilizing the morphology of nano-calcium carbonate. Under the ratio of the present invention, in addition to the needle-like structure of the modified nano-calcium carbonate itself, more complex surface structures may be formed on the surface of the nano-calcium carbonate or between the nano-calcium carbonates, which is beneficial to improving the diversion effect of the nano-calcium carbonate, thereby allowing the solvent and dispersant to enter the cosmetic soil layer faster, and the coloring material can be more stably colored.
[0027] The present invention also adds a certain amount of disodium ethylenediaminetetraacetate, which can form a multi-level stable structure with nickel stearate and various composite amino acids in keratin hydrolyzate, thereby improving the dispersion stability of nano calcium carbonate. Disodium ethylenediaminetetraacetate can provide additional coordination sites for the surface of nano calcium carbonate through chelation, making the surface modification more uniform and stable.
[0028] Furthermore, the preparation method of the pre-coating material comprises the following steps:
[0029] Step A1: dissolving nickel stearate in an ethanol solution, adding disodium ethylenediaminetetraacetic acid and keratin hydrolyzate, and stirring to mix evenly;
[0030] Step A2: mixing needle-shaped nano-calcium carbonate, ethanol and deionized water in proportion to obtain a slurry, and heating the slurry to 40-50° C.;
[0031] Step A3: Add the solution prepared in step A1 to the slurry in step A2, stir and mix for 8-10 hours, and then cool to room temperature.
[0032] Furthermore, a secondary pre-spraying is provided after the pre-coating material is sprayed and before the colorant is sprayed, and the coating material of the secondary pre-spraying includes the following components in parts by weight:
[0033] 50-100 parts of deionized water;
[0034] Ethanol 50-100 parts;
[0035] 20-35 parts of needle-shaped nano calcium carbonate.
[0036] The secondary coating material is applied after the pre-coating material, so that the needle-shaped nano-calcium carbonate on the surface of the cosmetic soil layer and the inside of the cosmetic soil near the surface are respectively a nano-calcium carbonate layer containing more relatively hydrophilicity and a nano-calcium carbonate layer containing more relatively lipophilicity from the outside to the inside along the thickness direction of the cosmetic soil. By making the needle-shaped calcium carbonate on the surface of the cosmetic soil layer and the inside of the cosmetic soil near the surface have a gradient difference in hydrophilicity and lipophilicity, it is helpful for the organic solvent and dispersant to firstly adsorb the colorant on the surface of the cosmetic soil layer through the large specific surface area of a large number of relatively hydrophilic needle-shaped nano-calcium carbonate layers after the colorant is sprayed, and then quickly guide these organic solvents and dispersants to penetrate into the cosmetic soil layer more quickly through the lipophilicity of the relatively lipophilic needle-shaped nano-calcium carbonate in the deeper layer of the cosmetic soil, and the iron red colorant can be adsorbed on the surface more stably, so that the iron red colorant can be colored faster and more clearly after the colorant is sprayed.
[0037] Furthermore, before the secondary pre-spraying step, the surface formed by the pre-coating material is polished.
[0038] The grinding step is conducive to forming a better connection between the secondary pre-sprayed coating material and the pre-coating material, thereby making the transition of the jointly formed needle-shaped calcium carbonate layer smoother, which is conducive to improving the penetration efficiency of the organic solvent and dispersant in the colorant.
[0039] Furthermore, the dispersant is hydrogenated castor oil.
[0040] Furthermore, the organic solvent is propylene glycol methyl ether acetate.
[0041] Furthermore, the defoaming agent is tributyl phosphate.
[0042] A method for preparing a high-adhesion and high-permeability ceramic ink comprises the following steps:
[0043] S1: Preparation of colorant;
[0044] (1) stirring an organic solvent, a dispersant and a defoamer for 1-2 hours to obtain an organic dispersion;
[0045] (2) Add iron red material and 2 / 3 of the organic dispersion into a ball mill and mill until D100 is 0.5-1 μm;
[0046] (3) adding the remaining organic dispersion and stirring evenly to obtain a coloring material;
[0047] S2: Preparation of pre-coating material.
[0048] A method for applying high-adhesion and high-permeability ceramic ink comprises the following steps:
[0049] Step B1: Apply the pre-coating material to the surface of the brick and dry it in the shade at room temperature; repeat 2-5 times;
[0050] Step B2: Printing the coloring material on the surface of the brick;
[0051] Step B3: spray the glaze onto the brick obtained in step B2 through a glaze spray cabinet.
[0052] Compared with the prior art, the present invention has the following beneficial effects:
[0053] The present invention uses a pre-spraying method to improve the permeability and adhesion of ceramic ink using needle-shaped nano calcium carbonate, thereby effectively solving the problem of glaze-ink separation. After the needle-shaped nano calcium carbonate in the pre-coating material penetrates into the cosmetic soil layer, it not only maintains the porosity in the layer, but also forms a high specific surface area on the surface, ensuring good adhesion of the colorant and avoiding edge seepage of the iron red material. Adding nickel stearate further improves the dispersibility and surface lipophilicity of calcium carbonate, which helps the organic solvent and dispersant in the colorant to penetrate faster. In addition, further by setting the optimization such as secondary pre-spraying, the needle-shaped calcium carbonate has a hydrophilic-lipophilic difference in gradient on the surface of the cosmetic soil layer and the inside of the cosmetic soil near the surface, so as to help the colorant to first adsorb the colorant by a large specific surface area of a large number of relatively hydrophilic needle-shaped nano calcium carbonate layers on the surface of the cosmetic soil layer after spraying, and then quickly guide these organic solvents and dispersants to penetrate into the cosmetic soil layer more quickly by the lipophilicity of the relatively lipophilic needle-shaped nano calcium carbonate at the deeper layer of the cosmetic soil, and the iron red material can be more stably adsorbed on the surface, further improving the clarity of the coloring effect and the printed pattern. The ceramic ink of the present invention has excellent adhesion and permeability, and significantly improves the clarity and resolution of the ceramic pattern. DETAILED DESCRIPTION
[0054] The present invention is described in detail below in conjunction with embodiments.
[0055] Example 1
[0056] A high-adhesion and high-permeability ceramic ink comprises a pre-coating material and a coloring material, wherein the pre-coating material is sprayed on the surface of the ceramic tile before the coloring material, and the coloring material is sprayed after the pre-coating material is dried; the specific steps are as follows:
[0057] Step B1: Apply the pre-coating material to the surface of the brick and dry it in the shade at room temperature; repeat 5 times;
[0058] Step B2: Printing the coloring material on the surface of the brick;
[0059] Step B3: spray the glaze onto the brick obtained in step B2 through a glaze spray cabinet.
[0060] Wherein, the coloring material comprises the following components in parts by weight:
[0061]
[0062] The dispersant is hydrogenated castor oil.
[0063] The organic solvent is propylene glycol methyl ether acetate.
[0064] The defoaming agent is tributyl phosphate.
[0065] The steps for preparing the colorant are as follows:
[0066] (1) stirring an organic solvent, a dispersant and a defoamer for 1 hour to obtain an organic dispersion;
[0067] (2) Add iron red material and 2 / 3 of the organic dispersion into a ball mill and mill until D100 is 0.5 μm;
[0068] (3) adding the remaining organic dispersion and stirring evenly to obtain a coloring material;
[0069] The pre-coating material includes the following components in parts by weight:
[0070] 50 parts of deionized water;
[0071] Ethanol 50 parts;
[0072] 20 parts of needle-shaped nano calcium carbonate.
[0073] The preparation method of the pre-coating material comprises the following steps: mixing needle-shaped nano calcium carbonate, ethanol and deionized water in proportion to obtain the pre-coating material.
[0074] Example 2
[0075] A high-adhesion and high-permeability ceramic ink comprises a pre-coating material and a coloring material, wherein the pre-coating material is sprayed on the surface of the ceramic tile before the coloring material, and the coloring material is sprayed after the pre-coating material is dried; the specific steps are as follows:
[0076] Step B1: Apply the pre-coating material to the surface of the brick and dry it in the shade at room temperature; repeat twice;
[0077] Step B2: Printing the coloring material on the surface of the brick;
[0078] Step B3: spray the glaze onto the brick obtained in step B2 through a glaze spray cabinet.
[0079] Wherein, the coloring material comprises the following components in parts by weight:
[0080]
[0081]
[0082] The dispersant is hydrogenated castor oil.
[0083] The organic solvent is propylene glycol methyl ether acetate.
[0084] The defoaming agent is tributyl phosphate.
[0085] The steps for preparing the colorant are as follows:
[0086] (1) stirring an organic solvent, a dispersant and a defoamer for 1 hour to obtain an organic dispersion;
[0087] (2) Add iron red material and 2 / 3 of the organic dispersion into a ball mill and mill until D100 is 0.5 μm;
[0088] (3) adding the remaining organic dispersion and stirring evenly to obtain a coloring material;
[0089] The pre-coating material includes the following components in parts by weight:
[0090] 100 parts of deionized water;
[0091] 100 parts of ethanol;
[0092] 35 parts of needle-shaped nano calcium carbonate.
[0093] The preparation method of the pre-coating material comprises the following steps: mixing needle-shaped nano calcium carbonate, ethanol and deionized water in proportion to obtain the pre-coating material.
[0094] Example 3
[0095] A high-adhesion and high-permeability ceramic ink comprises a pre-coating material and a coloring material, wherein the pre-coating material is sprayed on the surface of the ceramic tile before the coloring material, and the coloring material is sprayed after the pre-coating material is dried; the specific steps are as follows:
[0096] Step B1: Apply the pre-coating material to the surface of the brick and dry it in the shade at room temperature; repeat 4 times;
[0097] Step B2: Printing the coloring material on the surface of the brick;
[0098] Step B3: spray the glaze onto the brick obtained in step B2 through a glaze spray cabinet.
[0099] Wherein, the coloring material comprises the following components in parts by weight:
[0100]
[0101] The dispersant is hydrogenated castor oil.
[0102] The organic solvent is propylene glycol methyl ether acetate.
[0103] The defoaming agent is tributyl phosphate.
[0104] The steps for preparing the colorant are as follows:
[0105] (1) stirring an organic solvent, a dispersant and a defoamer for 1 hour to obtain an organic dispersion;
[0106] (2) Add iron red material and 2 / 3 of the organic dispersion into a ball mill and mill until D100 is 0.5 μm;
[0107] (3) adding the remaining organic dispersion and stirring evenly to obtain a coloring material;
[0108] The pre-coating material includes the following components in parts by weight:
[0109] 70 parts of deionized water;
[0110] Ethanol 80 parts;
[0111] 30 parts of needle-shaped nano calcium carbonate.
[0112] The preparation method of the pre-coating material comprises the following steps: mixing needle-shaped nano calcium carbonate, ethanol and deionized water in proportion to obtain the pre-coating material.
[0113] Example 4
[0114] A high-adhesion and high-permeability ceramic ink comprises a pre-coating material and a coloring material, wherein the pre-coating material is sprayed on the surface of the ceramic tile before the coloring material, and the coloring material is sprayed after the pre-coating material is dried; the specific steps are as follows:
[0115] Step B1: Apply the pre-coating material to the surface of the brick and dry it in the shade at room temperature; repeat 3 times;
[0116] Step B2: Printing the coloring material on the surface of the brick;
[0117] Step B3: spray the glaze onto the brick obtained in step B2 through a glaze spray cabinet.
[0118] Wherein, the coloring material comprises the following components in parts by weight:
[0119]
[0120] The dispersant is hydrogenated castor oil.
[0121] The organic solvent is propylene glycol methyl ether acetate.
[0122] The defoaming agent is tributyl phosphate.
[0123] The steps for preparing the colorant are as follows:
[0124] (1) stirring an organic solvent, a dispersant and a defoamer for 1 hour to obtain an organic dispersion;
[0125] (2) Add iron red material and 2 / 3 of the organic dispersion into a ball mill and mill until D100 is 0.5 μm;
[0126] (3) adding the remaining organic dispersion and stirring evenly to obtain a coloring material;
[0127] The pre-coating material includes the following components in parts by weight:
[0128] 100 parts of deionized water;
[0129] Ethanol 50 parts;
[0130] 20 parts of needle-shaped nano calcium carbonate.
[0131] The preparation method of the pre-coating material comprises the following steps: mixing needle-shaped nano calcium carbonate, ethanol and deionized water in proportion to obtain the pre-coating material.
[0132] Example 5
[0133] A high-adhesion and high-permeability ceramic ink comprises a pre-coating material and a coloring material, wherein the pre-coating material is sprayed on the surface of the ceramic tile before the coloring material, and the coloring material is sprayed after the pre-coating material is dried; the specific steps are as follows:
[0134] Step B1: Apply the pre-coating material to the surface of the brick and dry it in the shade at room temperature; repeat 5 times;
[0135] Step B2: Printing the coloring material on the surface of the brick;
[0136] Step B3: spray the glaze onto the brick obtained in step B2 through a glaze spray cabinet.
[0137] Wherein, the coloring material comprises the following components in parts by weight:
[0138]
[0139] The dispersant is hydrogenated castor oil.
[0140] The organic solvent is propylene glycol methyl ether acetate.
[0141] The defoaming agent is tributyl phosphate.
[0142] The steps for preparing the colorant are as follows:
[0143] (1) stirring an organic solvent, a dispersant and a defoamer for 1 hour to obtain an organic dispersion;
[0144] (2) Add iron red material and 2 / 3 of the organic dispersion into a ball mill and mill until D100 is 1 μm;
[0145] (3) adding the remaining organic dispersion and stirring evenly to obtain a coloring material;
[0146] The pre-coating material includes the following components in parts by weight:
[0147] 100 parts of deionized water;
[0148] 100 parts of ethanol;
[0149] 35 parts of needle-shaped nano calcium carbonate.
[0150] The preparation method of the pre-coating material comprises the following steps: mixing needle-shaped nano calcium carbonate, ethanol and deionized water in proportion to obtain the pre-coating material.
[0151] Example 6
[0152] A high-adhesion and high-permeability ceramic ink comprises a pre-coating material and a coloring material, wherein the pre-coating material is sprayed on the surface of the ceramic tile before the coloring material, and the coloring material is sprayed after the pre-coating material is dried; the specific steps are as follows:
[0153] Step B1: Apply the pre-coating material to the surface of the brick and dry it in the shade at room temperature; repeat 5 times;
[0154] Step B2: Printing the coloring material on the surface of the brick;
[0155] Step B3: spray the glaze onto the brick obtained in step B2 through a glaze spray cabinet.
[0156] Wherein, the coloring material comprises the following components in parts by weight:
[0157]
[0158] The dispersant is hydrogenated castor oil.
[0159] The organic solvent is propylene glycol methyl ether acetate.
[0160] The defoaming agent is tributyl phosphate.
[0161] The steps for preparing the colorant are as follows:
[0162] (1) stirring an organic solvent, a dispersant and a defoamer for 1 hour to obtain an organic dispersion;
[0163] (2) Add iron red material and 2 / 3 of the organic dispersion into a ball mill and mill until D100 is 0.5 μm;
[0164] (3) adding the remaining organic dispersion and stirring evenly to obtain a coloring material;
[0165] The pre-coating material includes the following components in parts by weight:
[0166]
[0167] The preparation method of the pre-coating material comprises the following steps:
[0168] Step A1: dissolving nickel stearate in an ethanol solution, adding disodium ethylenediaminetetraacetic acid and keratin hydrolyzate, and stirring to mix evenly;
[0169] Step A2: mixing needle-shaped nano-calcium carbonate, ethanol and deionized water in proportion to obtain a slurry, and heating the mixture to 40° C.;
[0170] Step A3: Add the nickel stearate solution prepared in step A1 to the slurry in step A2, stir and mix for 8 hours, and then cool to room temperature.
[0171] Example 7
[0172] A high-adhesion and high-permeability ceramic ink comprises a pre-coating material and a coloring material, wherein the pre-coating material is sprayed on the surface of the ceramic tile before the coloring material, and the coloring material is sprayed after the pre-coating material is dried; the specific steps are as follows:
[0173] Step B1: Apply the pre-coating material to the surface of the brick and dry it in the shade at room temperature; repeat 5 times;
[0174] Step B2: Printing the coloring material on the surface of the brick;
[0175] Step B3: spray the glaze onto the brick obtained in step B2 through a glaze spray cabinet.
[0176] Wherein, the coloring material comprises the following components in parts by weight:
[0177]
[0178] The dispersant is hydrogenated castor oil.
[0179] The organic solvent is propylene glycol methyl ether acetate.
[0180] The defoaming agent is tributyl phosphate.
[0181] The steps for preparing the colorant are as follows:
[0182] (1) stirring an organic solvent, a dispersant and a defoamer for 1 hour to obtain an organic dispersion;
[0183] (2) Add iron red material and 2 / 3 of the organic dispersion into a ball mill and mill until D100 is 0.5 μm;
[0184] (3) adding the remaining organic dispersion and stirring evenly to obtain a coloring material;
[0185] The pre-coating material includes the following components in parts by weight:
[0186]
[0187] The preparation method of the pre-coating material comprises the following steps:
[0188] Step A1: dissolving nickel stearate in an ethanol solution, adding disodium ethylenediaminetetraacetic acid and keratin hydrolyzate, and stirring to mix evenly;
[0189] Step A2: mixing needle-shaped nano-calcium carbonate, ethanol and deionized water in proportion to obtain a slurry, and heating the mixture to 50° C.;
[0190] Step A3: Add the nickel stearate solution prepared in step A1 to the slurry in step A2, stir and mix for 8 hours, and then cool to room temperature.
[0191] Example 8
[0192] A high-adhesion and high-permeability ceramic ink comprises a pre-coating material and a coloring material, wherein the pre-coating material is sprayed on the surface of the ceramic tile before the coloring material, and the coloring material is sprayed after the pre-coating material is dried; the specific steps are as follows:
[0193] Step B1: Apply the pre-coating material to the surface of the brick and dry it in the shade at room temperature; repeat 5 times;
[0194] Step B2: Printing the coloring material on the surface of the brick;
[0195] Step B3: spray the glaze onto the brick obtained in step B2 through a glaze spray cabinet.
[0196] Wherein, the coloring material comprises the following components in parts by weight:
[0197]
[0198] The dispersant is hydrogenated castor oil.
[0199] The organic solvent is propylene glycol methyl ether acetate.
[0200] The defoaming agent is tributyl phosphate.
[0201] The steps for preparing the colorant are as follows:
[0202] (1) stirring an organic solvent, a dispersant and a defoamer for 1 hour to obtain an organic dispersion;
[0203] (2) Add iron red material and 2 / 3 of the organic dispersion into a ball mill and mill until D100 is 0.5 μm;
[0204] (3) adding the remaining organic dispersion and stirring evenly to obtain a coloring material;
[0205] The pre-coating material includes the following components in parts by weight:
[0206]
[0207] The preparation method of the pre-coating material comprises the following steps:
[0208] Step A1: dissolving nickel stearate in an ethanol solution, adding disodium ethylenediaminetetraacetic acid and keratin hydrolyzate, and stirring to mix evenly;
[0209] Step A2: mixing needle-shaped nano-calcium carbonate, ethanol and deionized water in proportion to obtain a slurry, and heating the mixture to 40° C.;
[0210] Step A3: Add the nickel stearate solution prepared in step A1 to the slurry in step A2, stir and mix for 8 hours, and then cool to room temperature.
[0211] Example 9
[0212] A high-adhesion and high-permeability ceramic ink comprises a pre-coating material and a coloring material, wherein the pre-coating material is sprayed on the surface of the ceramic tile before the coloring material, and the coloring material is sprayed after the pre-coating material is dried; the specific steps are as follows:
[0213] Step B1: Apply the pre-coating material to the surface of the brick and dry it in the shade at room temperature; repeat 5 times;
[0214] Step B2: Printing the coloring material on the surface of the brick;
[0215] Step B3: spray the glaze onto the brick obtained in step B2 through a glaze spray cabinet.
[0216] Wherein, the coloring material comprises the following components in parts by weight:
[0217]
[0218] The dispersant is hydrogenated castor oil.
[0219] The organic solvent is propylene glycol methyl ether acetate.
[0220] The defoaming agent is tributyl phosphate.
[0221] The steps for preparing the colorant are as follows:
[0222] (1) stirring an organic solvent, a dispersant and a defoamer for 1 hour to obtain an organic dispersion;
[0223] (2) Add iron red material and 2 / 3 of the organic dispersion into a ball mill and mill until D100 is 0.5 μm;
[0224] (3) adding the remaining organic dispersion and stirring evenly to obtain a coloring material;
[0225] The pre-coating material includes the following components in parts by weight:
[0226]
[0227] The preparation method of the pre-coating material comprises the following steps:
[0228] Step A1: dissolving nickel stearate in an ethanol solution, adding disodium ethylenediaminetetraacetic acid and keratin hydrolyzate, and stirring to mix evenly;
[0229] Step A2: mixing needle-shaped nano-calcium carbonate, ethanol and deionized water in proportion to obtain a slurry, and heating the mixture to 40° C.;
[0230] Step A3: Add the nickel stearate solution prepared in step A1 to the slurry in step A2, stir and mix for 10 hours, and then cool to room temperature.
[0231] Example 10
[0232] A high-adhesion and high-permeability ceramic ink comprises a pre-coating material and a coloring material, wherein the pre-coating material is sprayed on the surface of the ceramic tile before the coloring material, and the coloring material is sprayed after the pre-coating material is dried; the specific steps are as follows:
[0233] Step B1: Apply the pre-coating material to the surface of the brick and dry it in the shade at room temperature; repeat 5 times;
[0234] Step B2: Printing the coloring material on the surface of the brick;
[0235] Step B3: spray the glaze onto the brick obtained in step B2 through a glaze spray cabinet.
[0236] Wherein, the coloring material comprises the following components in parts by weight:
[0237]
[0238] The dispersant is hydrogenated castor oil.
[0239] The organic solvent is propylene glycol methyl ether acetate.
[0240] The defoaming agent is tributyl phosphate.
[0241] The steps for preparing the colorant are as follows:
[0242] (1) stirring an organic solvent, a dispersant and a defoamer for 1 hour to obtain an organic dispersion;
[0243] (2) Add iron red material and 2 / 3 of the organic dispersion into a ball mill and mill until D100 is 0.5 μm;
[0244] (3) adding the remaining organic dispersion and stirring evenly to obtain a coloring material;
[0245] The pre-coating material includes the following components in parts by weight:
[0246]
[0247] The preparation method of the pre-coating material comprises the following steps:
[0248] Step A1: dissolving nickel stearate in an ethanol solution, adding disodium ethylenediaminetetraacetic acid and keratin hydrolyzate, and stirring to mix evenly;
[0249] Step A2: mixing needle-shaped nano-calcium carbonate, ethanol and deionized water in proportion to obtain a slurry, and heating the mixture to 50° C.;
[0250] Step A3: Add the nickel stearate solution prepared in step A1 to the slurry in step A2, stir and mix for 8 hours, and then cool to room temperature.
[0251] Embodiment 11
[0252] A high-adhesion and high-permeability ceramic ink comprises a pre-coating material and a coloring material, wherein the pre-coating material is sprayed on the surface of the ceramic tile before the coloring material, and the coloring material is sprayed after the pre-coating material is dried; the specific steps are as follows:
[0253] Step B1: Apply the pre-coating material to the surface of the brick and dry it in the shade at room temperature; repeat 5 times;
[0254] Step B2: applying the secondary pre-coating coating material to the surface of the brick, and drying in the shade at room temperature;
[0255] Step B2: Printing the coloring material on the surface of the brick;
[0256] Step B3: spray the glaze onto the brick obtained in step B2 through a glaze spray cabinet.
[0257] Wherein, the coloring material comprises the following components in parts by weight:
[0258]
[0259] The dispersant is hydrogenated castor oil.
[0260] The organic solvent is propylene glycol methyl ether acetate.
[0261] The defoaming agent is tributyl phosphate.
[0262] The steps for preparing the colorant are as follows:
[0263] (1) stirring an organic solvent, a dispersant and a defoamer for 1 hour to obtain an organic dispersion;
[0264] (2) Add iron red material and 2 / 3 of the organic dispersion into a ball mill and mill until D100 is 0.5 μm;
[0265] (3) adding the remaining organic dispersion and stirring evenly to obtain a coloring material;
[0266] The pre-coating material includes the following components in parts by weight:
[0267]
[0268] The preparation method of the pre-coating material comprises the following steps:
[0269] Step A1: dissolving nickel stearate in an ethanol solution, adding disodium ethylenediaminetetraacetic acid and keratin hydrolyzate, and stirring to mix evenly;
[0270] Step A2: mixing needle-shaped nano-calcium carbonate, ethanol and deionized water in proportion to obtain a slurry, and heating the mixture to 50° C.;
[0271] Step A3: Add the nickel stearate solution prepared in step A1 to the slurry in step A2, stir and mix for 8 hours, and then cool to room temperature.
[0272] The secondary pre-spray coating material includes the following components in parts by weight:
[0273] 100 parts of deionized water;
[0274] 100 parts of ethanol;
[0275] 35 parts of needle-shaped nano calcium carbonate.
[0276] Example 12
[0277] A high-adhesion and high-permeability ceramic ink comprises a pre-coating material and a coloring material, wherein the pre-coating material is sprayed on the surface of the ceramic tile before the coloring material, and the coloring material is sprayed after the pre-coating material is dried; the specific steps are as follows:
[0278] Step B1: Apply the pre-coating material to the surface of the brick and dry it in the shade at room temperature; repeat 5 times;
[0279] Step B2: applying the secondary pre-coating coating material to the surface of the brick, and drying in the shade at room temperature;
[0280] Step B2: Printing the coloring material on the surface of the brick;
[0281] Step B3: spray the glaze onto the brick obtained in step B2 through a glaze spray cabinet.
[0282] Wherein, the coloring material comprises the following components in parts by weight:
[0283]
[0284] The dispersant is hydrogenated castor oil.
[0285] The organic solvent is propylene glycol methyl ether acetate.
[0286] The defoaming agent is tributyl phosphate.
[0287] The steps for preparing the colorant are as follows:
[0288] (1) stirring an organic solvent, a dispersant and a defoamer for 1 hour to obtain an organic dispersion;
[0289] (2) Add iron red material and 2 / 3 of the organic dispersion into a ball mill and mill until D100 is 0.5 μm;
[0290] (3) adding the remaining organic dispersion and stirring evenly to obtain a coloring material;
[0291] The pre-coating material includes the following components in parts by weight:
[0292]
[0293] The preparation method of the pre-coating material comprises the following steps:
[0294] Step A1: dissolving nickel stearate in an ethanol solution, adding disodium ethylenediaminetetraacetic acid and keratin hydrolyzate, and stirring to mix evenly;
[0295] Step A2: mixing needle-shaped nano-calcium carbonate, ethanol and deionized water in proportion to obtain a slurry, and heating the mixture to 50° C.;
[0296] Step A3: Add the nickel stearate solution prepared in step A1 to the slurry in step A2, stir and mix for 8 hours, and then cool to room temperature.
[0297] The secondary pre-spray coating material includes the following components in parts by weight:
[0298] 50 parts of deionized water;
[0299] Ethanol 50 parts;
[0300] 20 parts of needle-shaped nano calcium carbonate.
[0301] Embodiment 13
[0302] A high-adhesion and high-permeability ceramic ink comprises a pre-coating material and a coloring material, wherein the pre-coating material is sprayed on the surface of the ceramic tile before the coloring material, and the coloring material is sprayed after the pre-coating material is dried; the specific steps are as follows:
[0303] Step B1: Apply the pre-coating material to the surface of the brick and dry it in the shade at room temperature; repeat 5 times;
[0304] Step B2: applying the secondary pre-coating coating material to the surface of the brick, and drying in the shade at room temperature;
[0305] Step B2: Printing the coloring material on the surface of the brick;
[0306] Step B3: spray the glaze onto the brick obtained in step B2 through a glaze spray cabinet.
[0307] Wherein, the coloring material comprises the following components in parts by weight:
[0308]
[0309] The dispersant is hydrogenated castor oil.
[0310] The organic solvent is propylene glycol methyl ether acetate.
[0311] The defoaming agent is tributyl phosphate.
[0312] The steps for preparing the colorant are as follows:
[0313] (1) stirring an organic solvent, a dispersant and a defoamer for 1 hour to obtain an organic dispersion;
[0314] (2) Add iron red material and 2 / 3 of the organic dispersion into a ball mill and mill until D100 is 0.5 μm;
[0315] (3) adding the remaining organic dispersion and stirring evenly to obtain a coloring material;
[0316] The pre-coating material includes the following components in parts by weight:
[0317]
[0318] The preparation method of the pre-coating material comprises the following steps:
[0319] Step A1: dissolving nickel stearate in an ethanol solution, adding disodium ethylenediaminetetraacetic acid and keratin hydrolyzate, and stirring to mix evenly;
[0320] Step A2: mixing needle-shaped nano-calcium carbonate, ethanol and deionized water in proportion to obtain a slurry, and heating the mixture to 50° C.;
[0321] Step A3: Add the nickel stearate solution prepared in step A1 to the slurry in step A2, stir and mix for 8 hours, and then cool to room temperature.
[0322] The secondary pre-spray coating material includes the following components in parts by weight:
[0323] 80 parts of deionized water;
[0324] Ethanol 80 parts;
[0325] 30 parts of needle-shaped nano calcium carbonate.
[0326] Embodiment 14
[0327] A high-adhesion and high-permeability ceramic ink comprises a pre-coating material and a coloring material, wherein the pre-coating material is sprayed on the surface of the ceramic tile before the coloring material, and the coloring material is sprayed after the pre-coating material is dried; the specific steps are as follows:
[0328] Step B1: Apply the pre-coating material to the surface of the brick and dry it in the shade at room temperature; repeat 5 times;
[0329] Step B2: applying the secondary pre-coating coating material to the surface of the brick, and drying in the shade at room temperature;
[0330] Step B2: Printing the coloring material on the surface of the brick;
[0331] Step B3: spray the glaze onto the brick obtained in step B2 through a glaze spray cabinet.
[0332] Wherein, the coloring material comprises the following components in parts by weight:
[0333]
[0334] The dispersant is hydrogenated castor oil.
[0335] The organic solvent is propylene glycol methyl ether acetate.
[0336] The defoaming agent is tributyl phosphate.
[0337] The steps for preparing the colorant are as follows:
[0338] (1) stirring an organic solvent, a dispersant and a defoamer for 1 hour to obtain an organic dispersion;
[0339] (2) Add iron red material and 2 / 3 of the organic dispersion into a ball mill and mill until D100 is 0.5 μm;
[0340] (3) adding the remaining organic dispersion and stirring evenly to obtain a coloring material;
[0341] The pre-coating material includes the following components in parts by weight:
[0342]
[0343]
[0344] The preparation method of the pre-coating material comprises the following steps:
[0345] Step A1: dissolving nickel stearate in an ethanol solution, adding disodium ethylenediaminetetraacetic acid and keratin hydrolyzate, and stirring to mix evenly;
[0346] Step A2: mixing needle-shaped nano-calcium carbonate, ethanol and deionized water in proportion to obtain a slurry, and heating the mixture to 50° C.;
[0347] Step A3: Add the nickel stearate solution prepared in step A1 to the slurry in step A2, stir and mix for 8 hours, and then cool to room temperature.
[0348] The secondary pre-spray coating material includes the following components in parts by weight:
[0349] 100 parts of deionized water;
[0350] Ethanol 50 parts;
[0351] 20 parts of needle-shaped nano calcium carbonate.
[0352] Embodiment 15
[0353] A high-adhesion and high-permeability ceramic ink comprises a pre-coating material and a coloring material, wherein the pre-coating material is sprayed on the surface of the ceramic tile before the coloring material, and the coloring material is sprayed after the pre-coating material is dried; the specific steps are as follows:
[0354] Step B1: Apply the pre-coating material to the surface of the brick and dry it in the shade at room temperature; repeat 5 times;
[0355] Step B2: applying the secondary pre-coating coating material to the surface of the brick, and drying in the shade at room temperature;
[0356] Step B2: Printing the coloring material on the surface of the brick;
[0357] Step B3: spray the glaze onto the brick obtained in step B2 through a glaze spray cabinet.
[0358] Wherein, the coloring material comprises the following components in parts by weight:
[0359]
[0360] The dispersant is hydrogenated castor oil.
[0361] The organic solvent is propylene glycol methyl ether acetate.
[0362] The defoaming agent is tributyl phosphate.
[0363] The steps for preparing the colorant are as follows:
[0364] (1) stirring an organic solvent, a dispersant and a defoamer for 1 hour to obtain an organic dispersion;
[0365] (2) Add iron red material and 2 / 3 of the organic dispersion into a ball mill and mill until D100 is 0.5 μm;
[0366] (3) adding the remaining organic dispersion and stirring evenly to obtain a coloring material;
[0367] The pre-coating material includes the following components in parts by weight:
[0368]
[0369] The preparation method of the pre-coating material comprises the following steps:
[0370] Step A1: dissolving nickel stearate in an ethanol solution, adding disodium ethylenediaminetetraacetic acid and keratin hydrolyzate, and stirring to mix evenly;
[0371] Step A2: mixing needle-shaped nano-calcium carbonate, ethanol and deionized water in proportion to obtain a slurry, and heating the mixture to 50° C.;
[0372] Step A3: Add the nickel stearate solution prepared in step A1 to the slurry in step A2, stir and mix for 8 hours, and then cool to room temperature.
[0373] The secondary pre-spray coating material includes the following components in parts by weight:
[0374] 100 parts of deionized water;
[0375] 100 parts of ethanol;
[0376] 32 parts of needle-shaped nano calcium carbonate.
[0377] Example 16
[0378] A high-adhesion and high-permeability ceramic ink comprises a pre-coating material and a coloring material, wherein the pre-coating material is sprayed on the surface of the ceramic tile before the coloring material, and the coloring material is sprayed after the pre-coating material is dried; the specific steps are as follows:
[0379] Step B1: Apply the pre-coating material to the surface of the brick and dry it in the shade at room temperature; repeat 5 times;
[0380] Step B2: firstly grind the surface of the brick formed by the pre-coating material in step B1, then apply the secondary pre-coating coating material on the surface of the brick, and dry it in the shade at room temperature;
[0381] Step B2: Printing the coloring material on the surface of the brick;
[0382] Step B3: spray the glaze onto the brick obtained in step B2 through a glaze spray cabinet.
[0383] Wherein, the coloring material comprises the following components in parts by weight:
[0384]
[0385] The dispersant is hydrogenated castor oil.
[0386] The organic solvent is propylene glycol methyl ether acetate.
[0387] The defoaming agent is tributyl phosphate.
[0388] The steps for preparing the colorant are as follows:
[0389] (1) stirring an organic solvent, a dispersant and a defoamer for 1 hour to obtain an organic dispersion;
[0390] (2) Add iron red material and 2 / 3 of the organic dispersion into a ball mill and mill until D100 is 0.5 μm;
[0391] (3) adding the remaining organic dispersion and stirring evenly to obtain a coloring material;
[0392] The pre-coating material includes the following components in parts by weight:
[0393]
[0394] The preparation method of the pre-coating material comprises the following steps:
[0395] Step A1: dissolving nickel stearate in an ethanol solution, adding disodium ethylenediaminetetraacetic acid and keratin hydrolyzate, and stirring to mix evenly;
[0396] Step A2: mixing needle-shaped nano-calcium carbonate, ethanol and deionized water in proportion to obtain a slurry, and heating the mixture to 50° C.;
[0397] Step A3: Add the nickel stearate solution prepared in step A1 to the slurry in step A2, stir and mix for 8 hours, and then cool to room temperature.
[0398] The secondary pre-spray coating material includes the following components in parts by weight:
[0399] 100 parts of deionized water;
[0400] Ethanol 50 parts;
[0401] 35 parts of needle-shaped nano calcium carbonate.
[0402] Embodiment 17
[0403] A high-adhesion and high-permeability ceramic ink comprises a pre-coating material and a coloring material, wherein the pre-coating material is sprayed on the surface of the ceramic tile before the coloring material, and the coloring material is sprayed after the pre-coating material is dried; the specific steps are as follows:
[0404] Step B1: Apply the pre-coating material to the surface of the brick and dry it in the shade at room temperature; repeat 5 times;
[0405] Step B2: Printing the coloring material on the surface of the brick;
[0406] Step B3: spray the glaze onto the brick obtained in step B2 through a glaze spray cabinet.
[0407] Wherein, the coloring material comprises the following components in parts by weight:
[0408]
[0409] The dispersant is hydrogenated castor oil.
[0410] The organic solvent is propylene glycol methyl ether acetate.
[0411] The defoaming agent is tributyl phosphate.
[0412] The steps for preparing the colorant are as follows:
[0413] (1) stirring an organic solvent, a dispersant and a defoamer for 1 hour to obtain an organic dispersion;
[0414] (2) Add iron red material and 2 / 3 of the organic dispersion into a ball mill and mill until D100 is 0.5 μm;
[0415] (3) adding the remaining organic dispersion and stirring evenly to obtain a coloring material;
[0416] The pre-coating material includes the following components in parts by weight:
[0417]
[0418] The preparation method of the pre-coating material comprises the following steps:
[0419] Step A1: dissolving nickel stearate in an ethanol solution, adding disodium ethylenediaminetetraacetate and stirring to mix well;
[0420] Step A2: mixing needle-shaped nano-calcium carbonate, ethanol and deionized water in proportion to obtain a slurry, and heating the mixture to 40° C.;
[0421] Step A3: Add the nickel stearate solution prepared in step A1 to the slurry in step A2, stir and mix for 8 hours, and then cool to room temperature.
[0422] Comparative Example
[0423] Comparative Example 1:
[0424] Wherein, the coloring material comprises the following components in parts by weight:
[0425]
[0426] The dispersant is hydrogenated castor oil.
[0427] The organic solvent is propylene glycol methyl ether acetate.
[0428] The defoaming agent is tributyl phosphate.
[0429] The steps for preparing the colorant are as follows:
[0430] (1) stirring an organic solvent, a dispersant and a defoamer for 1 hour to obtain an organic dispersion;
[0431] (2) Add iron red material and 2 / 3 of the organic dispersion into a ball mill and mill until D100 is 0.5 μm;
[0432] (3) Add the remaining organic dispersion and stir evenly to obtain the coloring material.
[0433] Detection Methods
[0434] Hair color test
[0435] 1) The grayscale of the pattern designed according to the ink effect file is 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100%. The ink prepared in the embodiment and the comparative example is printed by inkjet printing. The inkjet amount is 25g / m 2 ; Spray glaze, glaze specific gravity: 1.20g / mL; glaze amount: 300g / m 2 ; Firing temperature: 1200℃; Firing time: 30min.
[0436] Preparation of glaze slurry used in the examples and comparative examples:
[0437] Accurately weigh 100 g of glaze (formula: 49 parts by weight of albite, 6.5 parts by weight of limestone, 10.7 parts by weight of wollastonite, 5.5 parts by weight of dolomite, 6.4 parts by weight of zinc oxide, 3.8 parts by weight of aluminum oxide, 7 parts by weight of white corundum, 4.5 parts by weight of quartz powder, 4.6 parts by weight of kaolin, 2 parts by weight of frit), 0.1 g of CMC, 0.2 g of STPP, 100 g of water, and 300 g of ball stone, and put them into a clean ball mill, and put the ball mill into a fast ball mill for three minutes to obtain a glaze slurry;
[0438] Table 1
[0439]
[0440]
[0441] Conclusion: The above test results show that the ceramic ink prepared by the present invention is less likely to produce glaze-ink separation and has a higher color development effect. In addition, both pre-coating and secondary coating can further improve the effect of ceramic ink being less likely to produce glaze-ink separation.
[0442] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A high-adhesion and high-permeability ceramic ink, characterized in that: It includes a pre-coating material and a coloring material, wherein the pre-coating material is sprayed on the surface of the tile before the coloring material, and the coloring material is sprayed after the pre-coating material is dried; Wherein, the coloring material is composed of the following components in parts by weight: 30-50 parts of iron red material; 40-60 parts of organic solvent; Dispersant 4-10 parts; 1-5 parts of defoaming agent; The pre-coating material is composed of the following components in parts by weight: 50-100 parts of deionized water; Ethanol 50-100 parts; 20-35 parts of needle-shaped nano calcium carbonate; Nickel stearate 10-20 parts; 6-10 parts of disodium ethylenediaminetetraacetate; 5-8 parts of keratin hydrolyzate; After the pre-coating material is sprayed and before the colorant is sprayed, a secondary pre-coating is also provided, and the coating material of the secondary pre-coating is composed of the following components in parts by weight: 50-100 parts of deionized water; Ethanol 50-100 parts; 20-35 parts of needle-shaped nano calcium carbonate.
2. The high-adhesion and high-permeability ceramic ink according to claim 1, characterized in that: The preparation method of the pre-coating material comprises the following steps: Step A1: dissolving nickel stearate in an ethanol solution, adding disodium ethylenediaminetetraacetic acid and keratin hydrolyzate, and stirring to mix evenly; Step A2: mixing needle-shaped nano-calcium carbonate, ethanol and deionized water in proportion to obtain a slurry, and heating the slurry to 40-50° C.; Step A3: Add the solution prepared in step A1 to the slurry in step A2, stir and mix for 8-10 hours, and then cool to room temperature.
3. The high-adhesion and high-permeability ceramic ink according to claim 1, characterized in that: Before the secondary pre-spraying step, the surface formed by the pre-coating material is polished.
4. The high-adhesion and high-permeability ceramic ink according to claim 1, characterized in that: The dispersant is hydrogenated castor oil.
5. The high-adhesion and high-permeability ceramic ink according to claim 1, characterized in that: The organic solvent is propylene glycol methyl ether acetate.
6. The high-adhesion and high-permeability ceramic ink according to claim 1, characterized in that: The defoaming agent is tributyl phosphate.
7. A method for preparing a high-adhesion and high-permeability ceramic ink according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: Preparation of colorant; (1) Stir the organic solvent, dispersant and defoamer for 1-2 hours to obtain an organic dispersion; (2) Add iron red material and 2 / 3 of the organic dispersion into a ball mill and mill until D100 is 0.5-1 μm; (3) Add the remaining organic dispersion and stir evenly to obtain a coloring material; S2: Preparation of pre-coating material.
8. A method for applying a high-adhesion and high-permeability ceramic ink according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step B1: Apply the pre-coating material to the surface of the brick and dry it in the shade at room temperature; repeat 2-5 times; Step B2: Printing the coloring material on the surface of the brick; Step B3: spray the glaze onto the brick obtained in step B2 through a glaze spray cabinet.
Citation Information
Patent Citations
Inkjet printing method on inorganic base material
JP2004099432A